COVID‐19, Virtual Church Services and a New Temporary Geography of Home. (22nd June 2020) - Bryson, John R.; Andres, Lauren; Davies, Andrew
Abstract: The COVID‐19 pandemic and subsequent lockdown measures implemented by the United Kingdom government from 23 March 2020 led to unprecedented adaptations from individuals and communities including places of worship, their clergy and congregations. This paper through a multi‐disciplinary dialogue between human geography and theology explores the interrelations between place, space and the spiritual. It identifies the bricolage mechanisms that were developed rapidly by churches to shift towards providing virtual church services. This was an uncommon practice by Christian denominations in the UK. COVID‐19 changed the rules requiring new practices to emerge resulting in a new form of infrasecular space to emerge. Such rapid transformations through the provision of online services and virtual embeddedness blurred the lines between sacred and secular spaces. During virtual services, the minister's home is temporally linked to the homes of congregants forming an intersacred space. Homes and spaces within homes are transformed into temporary sacred spaces. Abstract : The Covid‐19 pandemic led to unprecedented adaptations by individuals and organisations as they responded to lockdown and social distancing. This paper explores the shift towards the provision of virtual church services and the emergence of a new form of intersacred space based on temporally linking the minister's home with the homes of congregants.